Delay presentation of congenital diaphragmatic hernia with gastrointestinal manifestations: A case report - Karimi, Babak; Khademi, Gholamreza; Abdollahpour, Nooshin; Imani, Bahareh; Mortezaee, Masoud (Iranian Journal of Pediatric Surgery, 2019)
Congenital diaphragmatic hernia (CDH) is usually accompanied by pulmonary hypoplasia, pulmonary hypertension, and other associated anomalies which result in high mortality rates in these cases. This condition occurs when there is a defect in the diaphragm (mostly to the left and posterolateral) from which herniation of the abdominal contents into the thorax can take place. Morgagni hernia is a less common CDH (only 5-10% of CDH cases), in which congenital herniation of the abdominal content through the triangular parasternal gaps of the anterior diaphragm happen. Morgagni hernia usually affects the right side, and the patients are usually asymptomatic. Herein, we present the case of a 15-month-old male infant with large Morgagni hernia resulting in poor weight gain. The presentation was unique due to its huge orifice, its gastrointestinal obstruction presentation and also its unremarkable radiologic findings. The patient was monitored by the follow up team for 12 months. The follow-up revealed no recurrence, and the patient had favorable weight gain without any gastrointestinal symptoms.